Interference between atomic Rb (5d5/2–5p3/2) and (5p3/2–5s1/2) coherences: observation of an exceptional point by quantum beating at ∼2.1 THz. (17th September 2021) - Goldshlag, W; Su, R; Park, S; Reboli, T O; Eden, J G
Abstract: Coupled oscillators are prevalent in nature and fundamental to fields as disparate as astrophysics, photonics, the mechanical sciences, and geophysics. Theory has identified singularities in the response of coupled oscillators, known as exceptional points (EPs), that are associated with non-Hermitian operators and lie at the transition between weak and strong coupling of the oscillator. Although several EPs have been reported or predicted to exist in nanophotonic resonators and Feshbach resonances, for example, tuning the phase of two interfering atomic or molecular coherences near an EP has not been demonstrated previously. We report the observation of an EP associated with a pair of interfering atomic coherences in Rb, oscillating at 386.3 and 384.2 THz, and confirm the theoretical prediction of an abrupt phase shift of ∼ π /4 as the EP is traversed by independently varying two experimental parameters. Pairs (and trios) of coupled coherences in thermal Rb atoms are established among the 7 s 1/2, 5 d 5/2, 5 p 3/2, and 5 s 1/2 states in pump–probe experiments with <200 fs laser pulses, and observed directly in the temporal and spectral domains through the ensuing quantum beating in the ∼2–36 THz interval. Interference between the (5 d 5/2 –5 p 3/2 ) and (5 p 3/2 –5 s 1/2 ) coherences is mediated by the 5 p 3/2 state and detected through quantum beating in the vicinity of the (5 d 5/2 –5 p 3/2 )–(5 p 3/2 –5 s 1/2 ) difference frequency of 2.11 THz which is monitored by a parametric four-wave mixing process. Phase of this composite atomic oscillator is first controlled by varying the mean Rb–Rb nearest neighbor distance (⟨ R ⟩) in a thermalized vapor. A discontinuous transition of (0.8 ± 0.2) ∼ π /4 radians in the phase of the coupled oscillator occurs when ⟨ R ⟩ is varied over the ∼80–90 nm interval, a phase shift associated with the transformation of a broadband, dissipative oscillator (characterized by a Fano interference window) into a strongly-coupled system resonant at 2.1 THz.